. - Cuneo, Ana María (Revista Chilena de Literatura, 2005)
This article accounts for the transition from an enigmatic style of writing characteristic of the modernity toward a form, in many cases more colloquial than that which Friedrich denominates contemporary poetry. It is a poetry which brings the empirical and the problematic subjects closer, with the intention of displaying situations that inside the text, become authentic revelations of being.